Case 3601: Spracklandus Hoser, 2009 (Reptilia, Serpentes, Elapidae): request for confirmation of the availability of the generic name and for the nomenclatural validation of the journal in which it was published - Hoser, Raymond (Bulletin of Zoological Nomenclature, 2013)
The purpose of this application, under Articles 78.2.3 and 80.2.1 of the Code, is to confirm that the generic name Spracklandus Hoser, 2009 [23 March] for the African spitting cobras is available in the sense of the Code, and also that the work in which this genus was proposed met the Code’s criteria of publication under Article 8.1. The Commission is asked to rule on these seemingly routine matters because widely promulgated recommendations by some herpetologists to use a junior objective synonym, Afronaja Wallach, Wüster & Broadley, 2009 [21 September], instead has resulted in instability in nomenclature.
Keywords: Nomenclature; taxonomy; Reptilia; ELAPIDAE; spitting cobras; Spracklandus; Afronaja